Pandangan Iqbal tentang Materi, Ruang, dan Waktu - Sudaryanto Sudaryanto (Jurnal Filsafat "WISDOM", 2003)
The concep of matter as a material thing atom or steady particle in time and space was replaced by relative theory with concept of matter as events system. The theory of modern physics has exchanged the meaning of "matter" bercome "organism" with rresult that, according to Iqbal's opinion, matter is derived from movement. The space could be distinguished between visible, mathematics, objective, absolute, and relative space. Time was also distinguished. Finally, Iqbal put those concepts in contact with the concept of self